COGNITIVE IMPAIRMENTS IN PATIENTS WITH PSORIASIS: A CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Psoriasis is a chronic inflammatory skin disorder that has been increasingly associated with cognitive dysfunction. However, the prevalence of mild cognitive impairment (MCI) in psoriasis patients remains underexplored. This study aims to assess the presence of MCI in individuals with psoriasis using the Montreal Cognitive Assessment (MoCA) and examine its correlation with disease severity. Objectives: To evaluate the presence of mild cognitive impairment in patients with psoriasis and compare it with healthy controls using the Montreal Cognitive Assessment (MoCA) scale. Methods: A cross-sectional study was conducted on 50 patients diagnosed with psoriasis and 50 age- and sex-matched healthy controls. Cognitive function was evaluated using the Montreal Cognitive Assessment (MoCA), with a cutoff score of